Conflict of interest in corporate legal relations involving a single-member executive body of a business entity - E. B. Abakumova (Russian Journal of Economics and Law)
Objective: to comprehensively analyze the civil-legal aspects of the legislative regulation of conflict of interests in corporate legal relations with the participation of a sole executive body of an economic entity, and to identify the promising areas for improving legislation in this area.Methods: the methodological basis of the research was the methods and techniques of formal logic, analysis, synthesis, induction, deduction, comparison; private scientific methods of legal research were also used: historical-legal, formal-legal, comparative-legal and others. Results: the paper identifies the stages of a conflict of interest development in corporate relations: a) the interests of corporate legal relations subjects may conflict with each other, but there is no possibility for the manifestation of this contradiction; b) the authorized person has the opportunity to perform any action that contradicts the interests of the corporation; c) the process of the authorized person performing an action that creates an opportunity for violating the interests of the company; d) the authorized person violates the interests of the represented legal entity, pursuing their own interests. Each stage of a conflict of interests development is characterized by its own methods of legal influence. In addition, the author comes to the conclusion that it is necessary to separate the management and control functions in business companies by creating a supervisory board as a control body and prohibiting the combination of positions in the supervisory board and in the executive body of the business company controlled by it. Therefore, it is advisable to legally stipulate the regulation on the mandatory inclusion of independent directors in the board of directors of public joint-stock companies. The amount of information on the powers of the sole executive body of an economic entity, currently provided in the Unified State Register of Legal Entities, is insufficient to ensure the necessary level of business transparency. In this regard, the article suggests one of the possible options for improving forms No. 11001 and 13014, submitted to the registration authority during the state registration of legal entities. At the same time, the paper substantiates the incorrectness of the legal definition of “interested party transaction” and suggests its replacement with the concept of “transaction with a conflict of interests”.Scientific novelty: the author has carried out a comprehensive theoretical reviewing of the status of the sole executive body of an economic entity, which made it possible to formulate proposals for improving specific legal provisions and mechanisms, as well as to identify the key scientific and applied directions for the further development of legislation on economic entities. Practical significance: the recommendations presented in the paper are aimed at solving the specific problems related to the legal regulation of conflicts of interest in corporate relations with the participation of a sole executive body of an economic entity, and can be used in scientific and rule-making activities.